A Review on the Therapeutic Potential of Creeping Woodsorrel Leaves (Oxalis corniculata L.) in Relation to its Secondary Metabolites - Yusuf, Marsha Afifah; Ramadhania, Zelika Mega (Indonesian Journal of Biological Pharmacy, 2024)
AbstractAs a tropical country with plenty of medicinal raw materials, Indonesia is one of the most significant users of medicinal plants in the world. One of the plants with many properties is creeping woodsorrel leaves (Oxalis corniculata L.), which have many therapeutic benefits. The sources for this review were collected through a literature study from Google Scholar, PubMed, and ResearchGate. After reviewing ten journals, 11 pharmacological activities of Oxalis corniculata were found, namely analgesic, anti-inflammatory, anti-pyretic, anti-Alzheimer, anti-diabetic, anti-biofilm, anti-cancer, anti-hepatic, hypoglycemic activity, Parkinson's disease, and antibiotic. The tests, including in vivo and in vitro experiments, as well as analyses using the Kyoto Gene and Genomic Encyclopedia (KEGG) and Gene Ontology (GO), showed positive results.Keywords: Asam Kecil Leaves, Secondary Metabolites, Oxalis corniculata, Pharmacological activityAbstrakSebagai negara tropis dengan banyak bahan baku obat, Indonesia adalah salah satu pengguna terbesar tumbuhan obat di dunia. Salah satu tanaman dengan banyak khasiat adalah daun asam kecil (Oxalis corniculata L.). yang terbukti memiliki banyak manfaat terapi. Sumber untuk review ini dikumpulkan melalui studi literatur dari Google Scholar, PubMed, dan ResearchGate. Setelah meninjau 10 jurnal, ditemukan 11 aktivitas farmakologis Oxalis corniculata, yaitu analgesik, anti-inflamasi, anti-piretik, anti-alzheimer, anti-diabetes, anti-biofilm, anti-kanker, anti-hepatik, aktivitas hipoglikemik, penyakit parkinson, dan anti-bakteri. Pengujian yang dilakukan, termasuk uji in vivo dan in vitro, serta analisis menggunakan Kyoto Gene and Genomic Encyclopedia (KEGG) dan Gene Ontology (GO), menunjukkan hasil yang positif.Kata kunci: Daun Asam Kecil, Aktivitas farmakologi, Metabolit Sekunder, Oxalis corniculata